2023
DOI: 10.1002/adfm.202304386
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Design of Functional Separators for Li Metal Batteries with Long‐Term Stability and High‐Rate Capability

Abstract: The lithium (Li) dendrite growth seriously hinders the applications of lithium metal batteries (LMBs). Numerous methods have been proposed to restrict the formation of Li dendrites by improving the Li‐ion transference number (tLi+) through separator modification according to Sand's time equation. However, ignoring the positive contribution of anion motion to solid electrolyte interphase (SEI) formation will result in insufficient inorganic components, which impedes practical implementation of LMBs. Herein, a “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…To address the challenges associated with interfacial impedance and Li dendrite growth, efforts have been directed at application of structured hosts, 23–25 deployment of artificial SEI, 26–28 design of functionalized separators, 29–31 and optimization of the electrolyte. 32–34 Amongst them, regulating the electrolyte formulation is the most effective approach for facilitating an intrinsically more stable SEI growth.…”
Section: Introductionmentioning
confidence: 99%
“…To address the challenges associated with interfacial impedance and Li dendrite growth, efforts have been directed at application of structured hosts, 23–25 deployment of artificial SEI, 26–28 design of functionalized separators, 29–31 and optimization of the electrolyte. 32–34 Amongst them, regulating the electrolyte formulation is the most effective approach for facilitating an intrinsically more stable SEI growth.…”
Section: Introductionmentioning
confidence: 99%
“…[84][85] Sand's time theory clearly has large relevance to metal batteries and has been applied in several works. [85][86][87][88][89] Bai, et al observed rapid onset dendritic growth and a spike in potential in capillary Li cells which corresponded to Sand's time when the current density was sufficiently high (see Figure 14a and b). [85] The apparent diffusion coefficient of the electrolyte (D app ) was calculated following Equation 11below, where t Sand is Sand's time, z c is the charge number of the metal cation, c 0 is the bulk salt concentration, F is Faraday's constant, J is the current density, and t a = 0.62 is the transference number of anions in the system.…”
Section: Sand's Time Theorymentioning
confidence: 99%
“…Sand's time theory clearly has large relevance to metal batteries and has been applied in several works [85–89] . Bai, et al.…”
Section: Growth‐related Models and Theorymentioning
confidence: 99%
“…25 These materials are well-suited for improving wettability and tuning the Li-ion flux. Unfortunately, both the pore structure construction and surface modification strategies usually occupy extra volume in the batteries, 14,19,24,26 and the synthesis methods of the coating materials and the coating process involve time-consuming and complex manufacturing processes that are not economically and industrially viable for large-scale production. 22,27 Therefore, a practicable separator modification strategy that is economically feasible and capable of tuning Li-ion transfer behavior is needed, even if the pore distribution is imperfect.…”
Section: Introductionmentioning
confidence: 99%